PRINCIPLES OF THE FINITE ELEMENT ANALYSIS IN THE DESIGN MODELLING OF THE METALLIC REMOVABLE DENTURES - Agop-Forna Doriana; Vasluianu Roxana; Andronache Monica; Caraş Cibela; Butnaru Moldoveanu Sînziana; Forna Norina (Romanian Dental Association for Education, 2019)
The optimal prosthetic therapeutic solution is influenced by topography and class of edentation, and by the biomechanical aspects corroborated with the morphologic support. FEA analysis can be performed for the assessment of the stability of removable denture and the stress levels at each clasp. The assessment of the stress distribution can be performed by using Autodesk Inventor Professional 2017. The support for temporomandibular joint for the simulation of the metallic removable dentures, can be made using Autodesk Simulation Mechanical 2014. The Poisson coefficient and the Young modulus of the materials of the removable dentures are used for FEA analysis. The bone tissues and the dental-periodontal units are considered elastic, liniar, homogenous, isotropic. To apply loading, vertical forces can be considered applied bilaterally and unilaterally on the removable denture, with a wide range of values, to simulate real values of masticatory forces. The forces can be applied using Autodesk Simulation Mechanical 2015. The knowledge of FEA principles by dental practitioners, can help in the widespread of finite element analysis in the optimisation of the design of removable dentures in the therapy of partially extended edentation.